Selective logging impacts on soil microbial communities and functioning in Bornean tropical forest - Robinson, Samuel J. B.; Elias, Dafydd M. O.; Goodall, Tim; Nottingham, Andrew T.; McNamara, Niall P.; Griffiths, Robert; Majalap, Noreen; Ostle, Nicholas J. (Frontiers in Microbiology, 2024)
Rainforests provide vital ecosystem services that are underpinned by plant-soil interactions. The forests of Borneo are globally important reservoirs of biodiversity and carbon, but a significant proportion of the forest that remains after large-scale agricultural conversion has been extensively modified due to timber harvest. We have limited understanding of how selective logging affects ecosystem functions including biogeochemical cycles driven by soil microbes. In this study we sampled soil from logging gaps and co-located intact lowland Dipterocarp rainforest in Borneo. We characterised soil bacterial and fungal communities and physicochemical properties, and determined soil functioning in terms of enzyme activity, nutrient supply rates and microbial heterotrophic respiration. Soil microbial biomass, alpha diversity and most soil properties and functions were resistant to logging. However, we found logging significantly shifted soil bacterial and fungal community composition, reduced the abundance of ectomycorrhizal fungi, increased the abundance of arbuscular mycorrhizal fungi, and reduced soil inorganic phosphorous concentration and nitrate supply rates, suggesting some down regulation of nutrient cycling. Within gaps, canopy openness was negatively related to ectomycorrhizal abundance and phosphomonoesterase activity and positively related to ammonium supply rates, suggesting control on soil phosphorus and nitrogen cycles via functional shifts in fungal communities. We found some evidence for reduced soil heterotrophic respiration with greater logging disturbance. Overall, our results demonstrate that while many soil microbial community attributes, soil properties and functions may be resistant to selective logging, logging can significantly impact the composition and abundance of key soil microbial groups linked to regulation of vital nutrient and carbon cycles in tropical forest.